Safety assessment of niacin in the US Food and Drug Administration's mini‐sentinel system. Issue 1 (6th November 2017) - Gagne, Joshua J.; Houstoun, Monika; Reichman, Marsha E.; Hampp, Christian; Marshall, James H.; Toh, Sengwee
Abstract: Purpose: The Heart Protection Study 2—Treatment of HDL to Reduce the Incidence of Vascular Events (HPS2‐THRIVE) trial found higher incidence rates of adverse reactions, including bleeding, in patients receiving the combination of extended‐release niacin and laropiprant versus placebo. It is not known whether these adverse events are attributable to laropiprant, not approved in the USA, or to extended‐release niacin. We compared rates of major gastrointestinal bleeding and intracranial hemorrhage among initiators of extended‐release niacin and initiators of fenofibrate. Methods: We used Mini‐Sentinel (now Sentinel) to conduct an observational, new user cohort analysis. We included data from 5 Data Partners covering the period from January 1, 2007 to August 31, 2013. Individuals who initiated extended‐release niacin were propensity score‐matched to individuals who initiated fenofibrate. Within the matched cohorts, we used Cox proportional hazards models to compare rates of hospitalization for major gastrointestinal bleeding events and intracranial hemorrhage assessed using validated claims‐based algorithms. Results: A total of 234 242 eligible extended‐release niacin initiators were identified, of whom 210 389 (90%) were 1:1 propensity score‐matched to eligible fenofibrate initiators. In propensity score‐matched analyses, no differences were observed between exposure groups in rates of major gastrointestinal bleeding (hazard ratio [HR], 0.98; 95% confidence interval [CI], 0.82 to 1.18) or intracranial hemorrhage (HR, 1.21; 95% CI, 0.66 to 2.22). Results were similar in pre‐specified sensitivity and subgroup analyses. Conclusions: We did not observe evidence for an association between extended‐release niacin versus fenofibrate and rates of major gastrointestinal bleeding or intracranial hemorrhage.